The impact of a ball sports combination training program on physical fitness and body mass Index in children with autism spectrum disorder - Mao, Hai-Yong; Qi, Kai; Meng, Shu-Qiao; Cai, Ke-Long; Zhu, Li-Na; Zhang, Wei-Ke; Qiao, Zhi-Yuan; Yang, Yang; Chen, Ai-Guo (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to explore the effects of a 12-week Ball Combination Training Program (BCTP) on the physical fitness and Body Mass Index (BMI) of children with Autism Spectrum Disorder (ASD).MethodsThis study employed a 2 × 2 mixed experimental design. A total of 29 children diagnosed with ASD were included (mean age = 7.60 ± 2.81). The 29 participants were randomly assigned to either the BCTP group (n = 15) or the control group (n = 14). The BCTP group underwent 12 weeks of ball combination exercise training (5 times per week, 45 min per session) in addition to their regular rehabilitation therapy, while the control group continued their usual rehabilitation therapy and daily activities. BMI and physical fitness tests were conducted before and after the 12-week intervention.ResultsThe 12-week BCTP prevented increase in BMI (p < 0.05), which increased in the control group. Children in the BCTP group also showed improvements in physical fitness, which was measured using the 2 × 10-meter shuttle run, sit-and-reach, and tennis ball throw (p < 0.05), while no such improvements were seen in the control group.ConclusionThe 12-week BCTP prevented an increase in BMI and improved the physical fitness of children with ASD in terms of speed, agility, flexibility, and upper body strength. Therefore, we recommend incorporating ball combination exercises into the physical rehabilitation of children with ASD to improve overall physical health and fitness.